Transformasi Perilaku Wisatawan dalam Aktivitas Pendakian Gunung: Motivasi, Mediasi Digital, dan Dinamika Sosial di Era Postmodern - Adhika Graha Irianto Putra; Mohammad Sapari Dwi Hadian; Awaludin Nugraha; Najla Raisa Maharani (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the transformation of tourist behavior in mountain hiking activities in the Sindoro, Sumbing, and Slamet (3S) area of Central Java within the context of nature-based tourism trends and digital mediation. A descriptive qualitative approach was employed, involving eight purposively selected hikers. Data were collected through semi-structured interviews, participant observation, and analysis of social media posts. The findings reveal a shift in motivation from physical challenge-oriented goals toward self-fulfillment, personal reflection, and psychological balance. Mountain hiking has also become normalized as part of an urban modern lifestyle. Furthermore, social media plays a significant role in shaping aspirations, documentation practices, and the reproduction of tourist behavior, extending the experience of nature beyond physical engagement into digital representation. These findings indicate that contemporary tourist behavior is constructed through the interaction of intrinsic motivation, social needs, and the logic of digital representation in nature-based tourism.